Fast pyrolysis of Beauty Leaf Fruit Husk (BLFH) in an auger reactor: Effect of temperature on the yield and physicochemical properties of BLFH oil. (July 2022) - Hasan, M.M.; Rasul, M.G.; Ashwath, N.; Khan, M.M.K.; Jahirul, M.I.
Abstract: This study investigated the effect of temperature on the yield and quality of pyrolysis oil produced from Beauty Leaf Fruit Husk (BLFH) using fast pyrolysis process. The BLFH was subjected to fast pyrolysis process using an auger reactor wherein the temperature was varied from 400 °C to 550 °C with 50 °C interval. The residence time of 3 min 20 s and the feedstock particle size of less than 1 mm were used in this study to produce bio-oil. The bio-oil yield was highest (∼45%) at 500 °C. At these conditions, the biochar and syngas yields were ∼33% and ∼22%, respectively. Analysis of the bio-oil showed the presence of 9 functional groups, with the phenol, aromatics and alcohol groups dominating the others. The amine group was present at the lowest concentration. It was also found that at 500 °C, concentration of carbon and the calorific val1ue were the highest and concentration of oxygen and water content were the lowest. The values of this combination of different elements and physicochemical properties can be referred as the best combination. The kinematic viscosity and density were decreased by around 15% and 7%, respectively as the pyrolysis temperature was increased from 400 °C to 550 °C. Other properties such as calorific value, flash point and cetane number did not exhibit substantial differences across the temperature treatments. Based on these results, it can be concluded that the BLFH will serve as a suitable source to produce renewable energy like bio-oil.